2021
DOI: 10.1097/md.0000000000028353
|View full text |Cite
|
Sign up to set email alerts
|

Emergent versus planned delivery in patients with placenta accreta spectrum disorders

Abstract: The aim of this study is to compare the clinical outcomes and to identify risk factors for emergent cesarean delivery and planned cesarean delivery in patients with placenta accreta spectrum (PAS) disorders in Vietnam. The medical records of patients admitted to our hospital with a diagnosis of PAS disorders >5 years were retrospectively reviewed. A total of 255 patients with PAS disorders were identified, including 95 cases in the emergent delivery group and 160 cases in the planned deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…1,3 Patients with PAS require hysterectomy and a longer hospital stay. 4 Today the main cause of PAS is uterine scar. This rise may be due to lack of expertise, shortage of time, patients' intolerant attitude, improper foetal assessment, and an over-conscious patient.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Patients with PAS require hysterectomy and a longer hospital stay. 4 Today the main cause of PAS is uterine scar. This rise may be due to lack of expertise, shortage of time, patients' intolerant attitude, improper foetal assessment, and an over-conscious patient.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen studies compared the birth weights between the PCD and ECD groups. [16][17][18][19][20][21][22][23][24][25]27,28,33] However, one study [16] reported the medians of birth weight in 3 gestational ranges and therefore could not be pooled. In comparison to the ECD group, the pooled birth weight was significantly higher in the PCD group (SMD: 1.64; 95% CI: 1.00-2.27; P < .001; I 2 = 97%).…”
Section: Neonatal Birth Weightmentioning
confidence: 99%
“…Nine studies reported the means of gestational age at delivery in the PCD and ECD gro ups. [18][19][20][21][22]24,25,27,33] The overall pooled estimate for gestational age was significantly higher in the PCD group compared to the ECD group (SMD: 2.20; 95% CI: 1.25-3.15; P < .001; I 2 = 98%). This finding was also seen in the subgroups of women with PP alone (SMD: 1.29; 95% CI: 1.02-1.56; P < .001; I 2 = 22%) and PAS patients with or without coexistent PP (SMD: 2.51; 95% CI: 1.21-3.81; P < .001; I 2 = 98%) (Fig.…”
Section: Quantitative Analysesmentioning
confidence: 99%
See 2 more Smart Citations